The combined effects of simulated microgravity and X-ray radiation on MC3T3-E1 cells and rat femurs - Jingjing Dong (Nature Portfolio, 2021)
Abstract Microgravity is well-known to induce Osteopenia. However, the combined effects of microgravity and radiation that commonly exist in space have not been broadly elucidated. This research investigates the combined effects on MC3T3-E1 cells and rat femurs. In MC3T3-E1 cells, simulated microgravity and X-ray radiation, alone or combination, show decreased cell activity, increased apoptosis rates by flow cytometric analysis, and decreased Runx2 and increased Caspase-3 mRNA and protein expressions. In rat femurs, simulated microgravity and X-ray radiation, alone or combination, show increased bone loss by micro-CT test and Masson staining, decreased serum BALP levels and Runx2 mRNA expressions, and increased serum CTX-1 levels and Caspase-3 mRNA expressions. The strongest effect is observed in the combined group in MC3T3-E1 cells and rat femurs. These findings suggest that the combination of microgravity and radiation exacerbates the effects of either treatment alone on MC3T3-E1 cells and rat femurs.